Mixture of Survival Analysis Models-Cluster-Weighted Weibull Distributions - Robert Csalodi; Zsolt Bagyura; Janos Abonyi (IEEE Access, 2021)
Survival analysis is a widely used method to establish a connection between a time to event outcome and a set of variables. The goal of this work is to improve the accuracy of the widely applied parametric survival models. This work highlights that accurate and interpretable survival analysis models can be identified by clustering-based exploration of the operating regions of local survival models. The key idea is that when operating regions of local Weibull distributions are represented by Gaussian mixture models, the parameters of the mixture-of-Weibull model can be identified by a clustering algorithm. The proposed method is utilised in three case studies. The examples cover studying the dropout rate of university students, calculating the remaining useful life of lithium-ion batteries, and determining the chances of survival of prostate cancer patients. The results demonstrate the wide applicability of the method and the benefits of clustering-based identification of local Weibull models.